Building educational relationships: an analysis of teacher interpersonal communication levels in two senior high schools - Novriyanti Achyar; Rini Sarianti; Ernie Novriyanti; Widiawati Widiawati (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
This study aims to map the level of teachers’ interpersonal communication in senior high schools as a basis for strengthening educational relationships. Using a quantitative descriptive approach, the study involved all 113 teachers from two senior high schools (49.5%) and SMA Negeri 3 Pariaman (50.5%) through a total sampling technique. Data were collected using a five-point Likert-scale questionnaire consisting of 25 items representing five indicators: openness and feedback, collaboration and teamwork, use of technology in communication, conflict management, and leadership supporting adaptive communication. Descriptive statistical analysis was applied to determine mean scores and achievement levels. The results indicate that teachers’ interpersonal communication is generally at a high level (mean = 3.81; 76.28%). Collaboration and teamwork emerged as the strongest dimension, followed by openness and feedback and leadership support, while communication technology use and conflict management showed relatively lower scores. This study contributes by providing an empirical mapping of teachers’ interpersonal communication as a foundation for strengthening professional relationships in secondary education. The findings imply the need for targeted professional development programs, particularly in conflict resolution and digital communication practices. However, this study is limited to two public senior high schools and relies on self-reported data, which may restrict the generalizability of the findings. Future research is recommended to involve broader samples and mixed-method approaches to gain deeper insights into interpersonal communication dynamics in schools.